Bugsy Siegel the dark side of the American dream - Shnayerson, Michael 1954- (Yale University Press, 2021)
The story of the notorious Jewish gangster who ascended from impoverished beginnings to the glittering Las Vegas strip";Fast-paced and absorbing. . . . With a keen eye for the amusing, and humanizing detail, [Shnayerson] enlivens the traditional rise-and-fall narrative.";-Jenna Weissman Joselit, New York Times Book Review";[A] brisk-reading chronicle.";-Tom Nolan, Wall Street Journal In a brief life that led to a violent end, Benjamin "Bugsy" Siegel (1906-1947) rose from desperate poverty to ill-gotten riches, from an early-twentieth-century family of Ukrainian Jewish immigrants on the Lower East Side to a kingdom of his own making in Las Vegas. In this captivating portrait, author Michael Shnayerson sets out not to absolve Bugsy Siegel but rather to understand him in all his complexity. Through the 1920s, 1930s, and most of the 1940s, Bugsy Siegel and his longtime partner in crime Meyer Lansky engaged in innumerable acts of violence. As World War II came to an end, Siegel saw the potential for a huge, elegant casino resort in the sands of Las Vegas. Jewish gangsters built nearly all of the Vegas casinos that followed. Then, one by one, they disappeared. Siegel's story laces through a larger, generational story of eastern European Jewish immigrants in the early- to mid-twentieth century
Keywords: Siegel, Benjamin -- 1906-1947; BIOGRAPHY & AUTOBIOGRAPHY / Criminals & Outlaws / bisacsh; Biografie